2014
DOI: 10.5657/kfas.2014.0103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Food Quality of Freshwater Rainbow Trout Oncorhynchus mykiss Cultured in Different Regions

Abstract: This study compared the food quality of freshwater rainbow trout Oncorhynchus mykiss cultured (in Pyeongchang, Pyeongtaek, Jecheon and Geochang) with that of imported salmon Oncorhynchus keta. The proximate composition of the four types of rainbow trout was 74.4-75.7% moisture, 18.3-19.4% crude protein, 3.1-4.3% crude lipid, and 1.3-1.7% ash. There were slight differences in the proximate composition of the four types of rainbow trout. No significant (P>0.05) differences were found in the red color and odor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Asparagine and glutamine are vulnerable to high temperature and they can transform to aspartic and glutamic acids by high temperature. Several researchers are either not analysed asparagine and glutamine (Chen et al, 2007;Kang et al, 2014;Mohanty et al, 2014;Unusan, 2007) or they stated that asparagine and glutamine are very low or none in the fish meat (Boonyoung et al, 2012;Dong et al, 2005;Rebolé et al, 2015;Sarma et al, 2013) contrary to aspartic acid and glutamic acid which are found highest amino acids, often (Özden, 2005;Park et al, 2006). Reason for this, asparagine and glutamine are directly affected by the severe conditions of the digestion process.…”
Section: Resultsmentioning
confidence: 99%
“…Asparagine and glutamine are vulnerable to high temperature and they can transform to aspartic and glutamic acids by high temperature. Several researchers are either not analysed asparagine and glutamine (Chen et al, 2007;Kang et al, 2014;Mohanty et al, 2014;Unusan, 2007) or they stated that asparagine and glutamine are very low or none in the fish meat (Boonyoung et al, 2012;Dong et al, 2005;Rebolé et al, 2015;Sarma et al, 2013) contrary to aspartic acid and glutamic acid which are found highest amino acids, often (Özden, 2005;Park et al, 2006). Reason for this, asparagine and glutamine are directly affected by the severe conditions of the digestion process.…”
Section: Resultsmentioning
confidence: 99%
“…Sample codes are the same as explained in Table 1. 2 The data were quoted from Kang et al (2014). 3 The values in parentheses indicate [(g of amino acid/100 g of total amino acid)]×100.…”
Section: 맛과 건강 기능mentioning
confidence: 99%
“…, Sample codes are the same as explained in Table 1. 2 The data were quoted from Kang et al (2014). 4 methionine histidine .…”
Section: 영양mentioning
confidence: 99%
See 2 more Smart Citations